The Repudiation in the Family Law of Tunisia, Moroco, Algeria, the United Arab Emirates and Jordan - Cervilla Garzón, María Dolores (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This paper carries out a comparative study from a gender perspective of the regulation of repudiation in the Family law of Tunisia, Morocco, Algeria, Jordan and the United Arab Emirates.